TANTANGAN TATA KELOLA SDM DI LEMBAGA PENDIDIKAN ISLAM: ANALISIS KEBIJAKAN PEMBINAAN DAN KARIR - Khairunnisa; Titi Kadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Human Resources (HR) governance is a key determinant of the quality and sustainability of Islamic educational institutions in the era of global competition. However, aspects of teacher development and career development are often hampered by management that is still conventional and not fully adaptive to the demands of modern educational professionalism. This condition results in low effectiveness of teacher management, limited opportunities for competency improvement, and a suboptimal reward and promotion system within Islamic educational institutions. This study aims to analyze the fundamental challenges in teacher development policies and career systems in Islamic educational institutions, particularly madrasas and Islamic boarding schools, while also identifying strategies for developing more professional and sustainable HR governance. The research method used is descriptive qualitative through literature studies and policy analysis by examining various regulations, previous research results, and documents related to the management of Islamic educational HR. The results of the study indicate that the main challenges include: (1) dualism of regulations between government policies and internal foundation policies that often lead to a lack of synchronization in teacher management; (2) the dominance of the service paradigm that tends to ignore aspects of professionalism, welfare, and appreciation for teacher performance; and (3) the absence of a structured, measurable, and transparent career path in the teacher development system. Furthermore, budget constraints, limited access to ongoing training, and minimal competency-based evaluations also hinder teacher quality development. This study concludes that Islamic educational institutions need to transform from family-based management to Competency-Based Human Resource Management (MSDM-BK) while still integrating Islamic values, professionalism, and an adaptive organizational culture. Implementing a planned development system, objective performance evaluation, and clear career development are believed to improve the motivation, loyalty, and quality of educators. This study recommends standardizing the professionalism system for job promotions, developing more transparent teacher career regulations, and allocating a dedicated budget for ongoing teacher competency development to support the overall improvement of the quality of Islamic education.